Improving Innovation Performance through Organizational Ambidexterity Approach and Absorptive Capacity Management: Evidence from Iran's defense industry - Kaveh Namvar; Alireza Bushehri; Seyed Kamal Tabaian; Abolfazl Bagheri (بهبود مدیریت, 2020)
Background and purpose: While evidence shows a significant effect of absorptive capacity on innovation around the world, no policy for improving absorptive capacity of defense firms has been adopted. As a result, a question arises that how increasing absorptive capacity of defense firms leads to increase their innovation performance. Defense customer’s needs made defense firms to incline more toward exploitation, but the owner of these firms-defense ministry is more inclined to exploration. The purpose of this study is to understand this duality and how absorptive capacity of these firms affect their parallel moves towards exploitative and explorative innovations. Methodology: this study is an applied research on purpose and from data gathering point of view is a mixed one. In qualitative part using 12 interview with experts of university and industries, a model and framework came up. In quantitative part based on 10 hypothesis on the study framework, 60 questionnaires has been gathered from different defense firms and its data went under analysis. Results: realized absorptive capacity affects exploitative and explorative innovations and ambidexterity, and that potential absorptive capacity mediates their relations. It was also shown that potential absorptive capacity is a prerequisite of realized absorptive capacity and ambidextrous defense firms have higher performance compared to other defense firms. Conclusion: policy makers should emphasize more on exploitation and realized absorptive capacity for firms in their maturity and decline life cycle. In other hand they should focus and invest on exploration and potential abortive capacity for firms in introduction and growth stage.